2021
DOI: 10.1001/jamanetworkopen.2021.5731
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trials Comparing Single-Enantiomer Drugs to Their Racemic Precursors

Abstract: Key Points Question How often do randomized clinical trials directly compare new single-enantiomer drugs to their existing racemic precursors, and how often are efficacy or safety differences observed? Findings In this systematic review of 15 single-enantiomer racemic drug pairs, 185 direct-comparison randomized clinical trials (median, 2 trials; interquartile range, 1-8 trials) were identified, 124 (67.0%) of which studied 1 drug pair. For 9 single-enantio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Along with other sensors of opioid signaling 11,27 , this study establishes the first genetically encoded fluorescent protein biosensor for an opioid drug, enabling real-time quantification. Furthermore, the enantioselectivity encourages biosensor development to investigate "chiral switching" of other drugs where a single enantiomer substitutes a clinically used racemate 28 . One enantiomer may serve previously unstudied indications.…”
Section: Below))mentioning
confidence: 99%
“…Along with other sensors of opioid signaling 11,27 , this study establishes the first genetically encoded fluorescent protein biosensor for an opioid drug, enabling real-time quantification. Furthermore, the enantioselectivity encourages biosensor development to investigate "chiral switching" of other drugs where a single enantiomer substitutes a clinically used racemate 28 . One enantiomer may serve previously unstudied indications.…”
Section: Below))mentioning
confidence: 99%
“…Furthermore, the enantioselectivity encourages biosensor development to investigate "chiral switching" of other drugs where a single enantiomer substitutes a clinically used racemate. 33 One enantiomer may serve previously unstudied indications. For example, S-methadone is now under clinical investigation as a rapidly acting antidepressant via nonopioid mechanism(s).…”
mentioning
confidence: 99%
“…Along with other sensors of opioid signaling, , this study establishes the first genetically encoded fluorescent protein biosensor for an opioid drug, enabling real-time quantification. Furthermore, the enantioselectivity encourages biosensor development to investigate “chiral switching” of other drugs where a single enantiomer substitutes a clinically used racemate . One enantiomer may serve previously unstudied indications.…”
mentioning
confidence: 99%
“…An interesting investigation was published in 2021 by Long et al in which randomized clinical trials directly comparing single-enantiomer drugs to a previously used racemic precursors for efficacy or safety differences were evaluated. Fifteen drugs subject to a chiral switch were evaluated, and for nine of them, no randomized clinical trials that showed enhanced effectiveness or safety when compared to their racemic predecessors were found [52]. It is interesting that more than half of these randomized clinical trials involved bupivacaine versus levobupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that more than half of these randomized clinical trials involved bupivacaine versus levobupivacaine. According to the findings of this systematic analysis, newly approved single-enantiomer medications are seldom directly compared to racemic precursors, and when they are, rarely have they been shown to deliver enhanced effectiveness or safety [52]. It should be acknowledged that the regulatory authorities do not have the legal authority to demand comparative effectiveness testing of single enantiomers to the previously registered racemates, prior to approval [9,49,52].…”
Section: Discussionmentioning
confidence: 99%